The “Oil-Spill Snorkel”: an innovative bioelectrochemical approach to accelerate hydrocarbons biodegradation in marine sediments - Cruz Viggi, Carolina; Presta, Enrica; Bellagamba, Marco; Kaciulis, Saulius; Balijepalli, Santosh K.; Zanaroli, Giulio; Petrangeli Papini, Marco; Rossetti, Simona; Aulenta, Federico (Frontiers in Microbiology, 2015)
This study presents the proof-of-concept of the “Oil-Spill Snorkel”: a novel bioelectrochemical approach to stimulate the oxidative biodegradation of petroleum hydrocarbons in sediments. The “Oil-Spill Snorkel” consists of a single conductive material (the snorkel) positioned suitably to create an electrochemical connection between the anoxic zone (the contaminated sediment) and the oxic zone (the overlying O2-containing water). The segment of the electrode buried within the sediment plays a role of anode, accepting electrons deriving from the oxidation of contaminants. Electrons flow through the snorkel up to the part exposed to the aerobic environment (the cathode), where they reduce oxygen to form water. Here we report the results of lab-scale microcosms setup with marine sediments and spiked with crude oil. Microcosms containing one or three graphite snorkels and controls (snorkel-free and autoclaved) were monitored for over 400 days. Collectively, the results of this study confirmed that the snorkels accelerate oxidative reactions taking place within the sediment, as documented by a significant 1.7-fold increase (p = 0.023, two-tailed t-test) in the cumulative oxygen uptake and 1.4-fold increase (p = 0.040) in the cumulative CO2 evolution in the microcosms containing three snorkels compared to snorkel-free controls. Accordingly, the initial rate of total petroleum hydrocarbons (TPH) degradation was also substantially enhanced. Indeed, while after 200 days of incubation a negligible degradation of TPH was noticed in snorkel-free controls, a significant reduction of 12 ± 1% (p = 0.004) and 21 ± 1% (p = 0.001) was observed in microcosms containing one and three snorkels, respectively. Although, the “Oil-Spill Snorkel” potentially represents a groundbreaking alternative to more expensive remediation options, further research efforts are needed to clarify factors and conditions affecting the snorkel-driven biodegradation processes and to identify suitable configurations for field applications.